Background risk and university endowment funds - Dimmock, Stephen G. (2013)
This paper tests the effect of background risk on university endowment portfolios, where background risk is defined as the volatility of universities' nonfinancial income. The results show that higher background risk is associated with lower portfolio standard deviations. Universities with higher background risk invest significantly more in fixed income and less in alternative assets. A 1 standard deviation increase in background risk increases the allocation to fixed income by approximately 15% relative to the mean. There is also evidence that wealthier, highly selective universities hold riskier portfolios.